Application of Gold Nanoparticles as Radiosensitizer for Metastatic Prostate Cancer Cell Lines - Soares, Sílvia (2023)
More than 50% of all prostate cancer (PCa) patients are treated by radiotherapy (RT). Radioresistance and cancer recurrence are two consequences of the therapy and are related to dose heterogeneity and non-selectivity between normal and tumoral cells. Gold nanoparticles (AuNPs) could be used as potential radiosensitizers to overcome these therapeutic limitations of RT. This study assessed the biological interaction of different morphologies of AuNPs with ionizing radiation (IR) in PCa cells. To achieve that aim, three different amine-pegylated AuNPs were synthesized with distinct sizes and shapes (spherical, AuNPsp-PEG, star, AuNPst-PEG, and rods, AuNPr-PEG) and viability, injury and colony assays were used to analyze their biological effect on PCa cells (PC3, DU145, and LNCaP) when submitted to the accumulative fraction of RT. The combinatory effect of AuNPs with IR decreased cell viability and increased apoptosis compared to cells treated only with IR or untreated cells. Additionally, our results showed an increase in the sensitization enhancement ratio by cells treated with AuNPs and IR, and this effect is cell line dependent. Our findings support that the design of AuNPs modulated their cellular behavior and suggested that AuNPs could improve the RT efficacy in PCa cells.